Thiol-based antioxidant supplementation alters human skeletal muscle signaling and attenuates its inflammatory response and recovery after intense eccentric exercise. - Michailidis, Yannis; Karagounis, Leonidas G; Terzis, Gerasimos; Jamurtas, Athanasios Z; Spengos, Kontantinos; Tsoukas, Dimitrios; Chatzinikolaou, Athanasios; Mandalidis, Dimitrios; Stefanetti, Renae J; Papassotiriou, Ioannis; Athanasopoulos, Spyros; Hawley, John A; et al. (Am J Clin Nutr, 2013)
BACKGROUND: The major thiol-disulfide couple of reduced glutathione (GSH) and oxidized glutathione is a key regulator of major transcriptional pathways regulating aseptic inflammation and recovery of skeletal muscle after aseptic injury. Antioxidant supplementation may hamper exercise-induced cellular adaptations. OBJECTIVE: The objective was to examine how thiol-based antioxidant supplementation affects skeletal muscle's performance and redox-sensitive signaling during the inflammatory and repair phases associated with exercise-induced microtrauma. DESIGN: In a double-blind, crossover design, 10 men received placebo or N-acetylcysteine (NAC; 20 mg · kg(-1) · d(-1)) after muscle-damaging exercise (300 eccentric contractions). In each trial, muscle performance was measured at baseline, after exercise, 2 h after exercise, and daily for 8 consecutive days. Muscle biopsy samples from vastus lateralis and blood samples were collected before exercise and 2 h, 2 d, and 8 d after exercise. RESULTS: NAC attenuated the elevation of inflammatory markers of muscle damage (creatine kinase activity, C-reactive protein, proinflammatory cytokines), nuclear factor κB phosphorylation, and the decrease in strength during the first 2 d of recovery. NAC also blunted the increase in phosphorylation of protein kinase B, mammalian target of rapamycin, p70 ribosomal S6 kinase, ribosomal protein S6, and mitogen activated protein kinase p38 at 2 and 8 d after exercise. NAC also abolished the increase in myogenic determination factor and reduced tumor necrosis factor-α 8 d after exercise. Performance was completely recovered only in the placebo group. CONCLUSION: Although thiol-based antioxidant supplementation enhances GSH availability in skeletal muscle, it disrupts the skeletal muscle inflammatory response and repair capability, potentially because of a blunted activation of redox-sensitive signaling pathways. This trial was registered at clinicaltrials.gov as NCT01778309.
Keywords: Acetylcysteine; Adaptation, Physiological; Adult; Antioxidants; Biomarkers; C-Reactive Protein; Creatine kinase; Cross-Over Studies; Cytokines; Diet; Dietary Supplements; Double-Blind Method; Exercise; glutathione; Humans; Immunohistochemistry; Inflammation; Male; Muscle Contraction; NF-kappa B; p38 Mitogen-Activated Protein Kinases; Phosphorylation; Proto-Oncogene Proteins c-akt; Quadriceps Muscle; Ribosomal Protein S6; Ribosomal Protein S6 Kinases, 70-kDa; signal transduction; Sulfhydryl Compounds; Tumor Necrosis Factor-alpha; Young Adult